International Emissions Trading and Induced Carbon-Saving Technical Change : Effects of Restricting the Trade in Carbon Rights - Patrick Matschoss; Heinz Welsch (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
This paper examines the implications of restricting the tradability of carbon rights in the presence of induced technical change. Unlike earlier approaches aiming at exploring the tradability-technology linkage we focus on climate-relevant 'carbon-saving' technical change. This is achieved by incorporating endogenous investment in carbon productivity into the RICE-99 integrated assessment model of Nordhaus and Boyer (2000). Simulation analysis of various emission reduction scenarios with several restrictions on emissions trading reveals a pronounced dichotomy of effects across regions: Restrictions to trading raise the investments in carbon productivity in permit demanding regions while reducing them in permit supplying regions. In terms of per capita consumption, permit demanding regions lose and permit supplying regions gain from restrictions. In scenarios that involve 'hot air', restrictions to trade lower overall emissions which results in reduced climate damage for most regions. Reduced damage, in turn, reduces the incentive to invest in carbon productivity.
Keywords: 330; carbon-saving technological progress; emissions trading; flexibility mechanism; induced technological change; integrated assessment model; Kohlendioxid; Emissionshandel; Regulierung; Klimaschutz; Technischer Fortschritt; Simulation; Endogener technischer Fortschritt; Welt; RICE model